Collapsing the Space That Divides Us with Community Engaged Literacies. Issue 5 (20th December 2021) - Rust, Julie; Brown, Carolyn; Ballard, Sarah
Abstract: Too often, our reading lists center one‐size‐fits‐all authors and experiences that don't make space for the wide array of cultures and histories that enliven our classrooms. Too often, our schools operate as if on an island, largely unaware of what is happening next door. Community engaged literacies, meaning‐making opportunities connecting local groups around historically‐steeped issues of local interest, offer one antidote to these common missteps. To illustrate, we share the story of one simple collaboration engaging two English classes from different schools in a zoom‐mediated conversation about a locally‐situated text.